Strategic public procurement: An overview - Heinz Handler (WWWforEurope, 2015)
The paper provides an overview of the development of public procurement (PP) rules in the EU and in selected international organisations. The EU rules were originally designed to foster competition and efficiency, and the dominant award criterion was the price. Over time, and in particular in the context of the "EU 2020" strategy, PP rules have been extended to address not only economic objectives, but also social and environmental goals as well as innovation aspects. As a result, such "strategic" elements of PP have in 2014 been legalised by the new EU Procurement Directives. However, as long as strategic PP remains an isolated policy, it will have only limited ramifications on Community-wide sustainability. Strategic PP should rather complement sustainability policies in their respective areas and should thus become an integral part of overall EU policies.
Keywords: H57; O38; 330; Public procurement; EU internal market; Europe 2020 strategy; sustainability; innovation